An unusual case in which a perforated Meckel's diverticulum became trapped in a pericecal hernia: A rare complication of Meckel's diverticulum - Satohiko Yanagisawa; Yasuhide Morikawa; Mototoshi Kato (Elsevier, 2015)
An 11-year-old boy had previously been diagnosed with repeated Meckel's diverticulitis at another hospital. Emergency laparoscopy was performed under general anesthesia, and an inflammatory mass was seen in the ileocecal region of the mesentery. However, no Meckel's diverticulum (MD) was observed, and so the patient was diagnosed with lymphadenitis. Three days after the operation, he developed anemia and gastrointestinal bleeding of unknown origin. Thus, he was transferred to our hospital for further investigation and to have his gastrointestinal bleeding treated. Based on imaging scans obtained at the previous hospital, a paraduodenal hernia was suspected, but no paraduodenal hernia was detected during emergency surgery, despite the fact that the full length of the normal small intestine could be traced. However, an inflammatory mass was observed, and the ileum appeared to be incarcerated in a pericecal hernia. We could not identify which portion of the intestine had become entrapped or reduce the hernia due to adhesion. The inflammatory mass was removed by ileocecal resection, and a pathological examination revealed that the entrapped portion of the intestine was an MD that had branched off from the small intestine immediately proximal to the ileocecal valve. The MD had perforated in the hernia sac, which had caused the patient's bleeding.